2011
DOI: 10.3201/eid1711.101893
|View full text |Cite
|
Sign up to set email alerts
|

New Dengue Virus Type 1 Genotype in Colombo, Sri Lanka

Abstract: The number of cases and severity of disease associated with dengue infection in Sri Lanka has been increasing since 1989, when the first epidemic of dengue hemorrhagic fever was recorded. We identified a new dengue virus 1 strain circulating in Sri Lanka that coincided with the 2009 dengue epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 13 publications
4
46
0
Order By: Relevance
“…Consistent with the known epidemiologic history of DENV infection in Sri Lanka (28)(29)(30) and the notion of original antigenic sin, we see that, whereas serotype-specific responses predominate for DENV2, there is a shift toward conserved epitopes for DENV3 and DENV1 responses, compatible with the epidemiologic data that indicate that initial infection is most likely caused by DENV2 and thus expansion of T cells recognizing conserved epitopes following infection with the more recently prevalent serotypes DENV1 and -3. In the case of DENV4, the same trend, albeit not statistically significant, was observed.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with the known epidemiologic history of DENV infection in Sri Lanka (28)(29)(30) and the notion of original antigenic sin, we see that, whereas serotype-specific responses predominate for DENV2, there is a shift toward conserved epitopes for DENV3 and DENV1 responses, compatible with the epidemiologic data that indicate that initial infection is most likely caused by DENV2 and thus expansion of T cells recognizing conserved epitopes following infection with the more recently prevalent serotypes DENV1 and -3. In the case of DENV4, the same trend, albeit not statistically significant, was observed.…”
Section: Discussionsupporting
confidence: 72%
“…The knowledge of the origin of epitopes allowed interpreting the data in context of the epidemiological history of Sri Lanka. The known historical prevalence of DENV serotypes circulating in Sri Lanka indicates that, whereas DENV2 has historically always been prevalent in Sri Lanka, recent years have seen the appearance of new substrains of DENV3 Lanka (28,29), and DENV1 has only recently appeared in this population (30). Accordingly, we hypothesized that original antigenic sin should dictate that the ratio of serotype specific to conserved responses should be decreased when comparing DENV2 (the "original" antigen) with other serotypes.…”
Section: Resultsmentioning
confidence: 99%
“…20,21 Dengue epidemics in the region have been linked to more intense transmission, expansion of the range of the virus, and introduction of new strains. [17][18][19][20][21] Most estimates of dengue incidence in the region are based on hospital-based studies and nationally reported cases, which grossly underestimate the true burden of disease and infection. 31 We followed a cohort of 799 children in Colombo, Sri Lanka, and estimated the incidence of infection and disease to be 8.39 and 3.38 cases/100 children, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…17 This increase in cases has been attributed to introduction of new genotypes of DENV, as well the expansion of the range of the virus on the island. [17][18][19] In many ways, the changing epidemiology of dengue in Sri Lanka mirrors events in other parts of the subcontinent including India, which has also documented large increases in cases and appearance of new virus strains. 20,21 We conducted a population-based study to determine the incidence of symptomatic and asymptomatic DENV infection among children living in Colombo, Sri Lanka, an urban setting of the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In 2009, the arrival of a new DENV-1 viral strain coincided with the largest DHF epidemic (346 deaths) since dengue was made a reportable disease in 1996. 11,12 Dengue disease has reached epidemic proportions in Sri Lanka every year since 2009, 13 and DENV-1 has remained the predominant disease-causing serotype (Sirisena 14 and A. D. De Silva, unpublished data). In 2012 in Sri Lanka, there were 44,456 reported cases of clinically diagnosed dengue disease, of which over 10,000 cases were in the capital city of Colombo.…”
Section: Introductionmentioning
confidence: 99%